The Effect of Content Feeding on Electronic Word of Mouth (E-WOM)Activities Mediatedby Information Dissemination - Zakaria Wahab; Eko Mohammad Fitrianto; Agustina Hanafi (Jurnal Manajemen Indonesia, 2022)
This research was conducted to examine the mediating role of information dissemination (seeding) in the relation between marketing campaigns (content feeding) and electronic word of mouth (eWOM). The research object is three marketing campaigns from three online marketplaces in Indonesia, named: Shopee, Tokopedia, and Bukalapak. A model was built to test and evaluate and test the mediation effect existence. The number of participants was involved in this research is 200 participants, and they answer the specific question related to the research. We found that all regression path in the models is significant, that indicate direct and indirect effect happened simultaneously. Our conclusion is information dissemination (seeding activity) playing an important role as a partial mediating variable. Other implications and future research discussed. Keywords — E-WoM, Marketing Campaign, Content Feeding, Content Seeding